2013
DOI: 10.4103/2229-5151.124161
|View full text |Cite
|
Sign up to set email alerts
|

Use of dexmedetomidine to facilitate non-invasive ventilation

Abstract: Patients with chronic obstructive pulmonary disease and congestive heart failure exacerbations, as well as pneumonia benefit from the use of non-invasive ventilation (NIV), due to increased patient comfort and a reduced incidence of ventilator-associated pneumonia. However, some patients do not tolerate NIV due to anxiety or agitation, and traditionally physicians have withheld sedation from these patients due to concerns of loss of airway protection and respiratory depression. We report our recent experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Patients did not usually receive sedatives. If they were agitated and uncomfortable with the mask, intravenous morphine or dexmedetomidine was initiated [ 17 ]. All patients were monitored with continuous electrocardiography and SpO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Patients did not usually receive sedatives. If they were agitated and uncomfortable with the mask, intravenous morphine or dexmedetomidine was initiated [ 17 ]. All patients were monitored with continuous electrocardiography and SpO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…A case report of a 91-year-old man with COPD on non-invasive ventilation states that dexmedetomidine facilitated non-invasive ventilation and reduced the hospital stay. 17 A phase II study by Venn et al 18 concluded that the use of dexmedetomidine to perform rescue intubation in patients reduced the propofol dose, as well as causing a slight decrease in blood pressure, heart rate, and heart output volume, and did not cause any complications after discontinuation. Although the design of this study was not similar to ours, a reduction in blood pressure in patients receiving dexmedetomidine was seen in our study as well; however, we did not observe any effect on patients' heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…A case report of a 91-year-old man with COPD on non-invasive ventilation states that dexmedetomidine facilitated non-invasive ventilation and reduced the hospital stay [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…NIV is useful for many cases, but only a few patients could tolerate this procedure due to the discomfort of using this type of ventilation. Therefore, some studies found that using sedation during NIV technique should be considered to reduce the percentage of NIV failure and comfort the patient during NIV (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) . Some studies reported that NIV was challenging to apply in the Intensive Care Unit (ICU) because of patient agitation (4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%